Traditional Art Kayori as An Identity of Taa Society in District of Tojo Una-Una in Globalization Era - Hasan, Abdul Rasyid (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2015)
Kayori is someone’s or group’s statement expressed civilly in a particular time, so that the messages delivered are easily internalized and understood to nod in agreement. This research intends to identify form, function, and meaning contained in kayori traditional art of Taa society. This research employed qualitative method with a cultural approach. The results of this study portray that kayori performance periodically held is an introduction media in increasing public awareness. Kayori, embracing aesthetic values, functions to diffuse moral and aesthetic aspects to the society. Education in kayori tradition follows the regeneration process in to society orientating towards the new roles for young generation to maintain their cultural heritages. Kayori tradition implies valuable meaning of life and provides chance in understanding historical cultural heritages in tackling down recent issues in Taa society.